THE THEODICY TRAP. Issue 44 (30th September 2016) - Cahn, Steven M.
Abstract : A theodicy is shaky if it explains only some evils but not all. For if certain possible evils are inconsistent with the existence of God, then their occurrence would disprove theism. But if a theodicy offers a justification for all possible evils, then it leads into a trap. After all, if God's existence is compatible with every horrible occurrence imaginable, why should belief in God afford any comfort?